Do cross-default and cross-collateral clause fulfill the principles of justice and equality in loan agreement? (the case of Indonesia) - Suwinto Johan; Amad Sudiro; Ariawan Gunadi (Global Business & Finance Review (GBFR), 2022)
Purpose: This research seeks to examine the cross-default and cross-collateral clauses in loan agreement that meet the principles of justice and the principle of balance, especially in developing countries such as Indonesia. Design/methodology/approach: A legal normative review method is used in this study. The cross-default clause and cross-collateral clauses are discussed in relation to existing legal practices in this paper, and a new framework is proposed. The topic in the research centers on the principles of justice and equality for creditors and borrowers. Findings: It concludes that the cross-default and cross-collateral clauses do not fulfill the principles of justice and balance. Cross-default clause shows injustice when associated with subsidiaries' performance. Cross-collateral clause does not fulfill the principle of equality because it has a higher collateral execution position than other non-bank creditors or non-cash management services bank. This study suggests that debtors reconsider the provision of cross-default and cross-collateral clauses. Cross-default can be limited to a minimum default value. Cross-collateral must be abolished to deliver justice to all creditors. Research limitations/implications: The pre-lamination of this research is that it does not address the issue of negotiations between creditors and debtors. Finally, existing creditors are unlikely to change the rights they have already obtained. Further research can be developed by researching the types of businesses that provide a fixed asset guarantee value. Originality/value: This study provides a novelty by rethinking principle of fairness and equality in cross-collateral and cross-default clauses in loan agreement, under insolvency.
Keywords: 650; Default; Equality; Justice; Loan Agreement